Canonical Wnt Signaling Promotes Neovascularization Through Determination of Endothelial Progenitor Cell Fate via Metabolic Profile Regulation. (22nd July 2019) - Shao, Yan; Chen, Jianglei; Freeman, Willard; Dong, Li-Jie; Zhang, Zhi-Hui; Xu, Manhong; Qiu, Fangfang; Du, Yanhong; Liu, Juping; Li, Xiao-Rong; Ma, Jian-Xing
Abstract: Endothelial progenitor cells (EPCs) contribute to blood vessel formation. Canonical Wnt signaling plays an important role in physiological and pathological angiogenesis and EPC fate regulation. However, the mechanism for Wnt signaling to regulate EPC fate in neovascularization (NV) has not been clearly defined. Here, we showed that very low-density lipoprotein receptor knockout ( Vldlr −/− ) mice, a model of ocular NV induced by Wnt signaling overactivation, have increased EPC numbers in the bone marrow, blood, and retina, as well as an elevated mitochondrial membrane potential indicating higher mitochondrial function of EPCs in the circulation. Isolated EPCs from Vldlr −/− mice showed overactivated Wnt signaling, correlating with increased mitochondrial function, mass, and DNA copy numbers, compared with WT EPCs. Our results also demonstrated that Wnt signaling upregulated mitochondrial biogenesis and function, while inhibiting glycolysis in EPCs, which further decreased EPC stemness and promoted EPCs to a more active state toward differentiation, which may contribute to pathologic vascular formation. Fenofibric acid, an active metabolite of fenofibrate, inhibited Wnt signaling and mitochondrial function in EPCs and decreased EPC numbers in Vldlr −/− mice. It also decreased mitochondrial biogenesis and reactive oxygen species production in Vldlr −/− EPCs, which may be responsible for its therapeutic effect on diabetic retinopathy. These findings demonstrated that Wnt signaling regulates EPC fate through metabolism, suggesting potential application of the EPC metabolic profile as predictor and therapeutic target for neovascular diseases. Stem Cells   2019;37:1331–1343 : Abstract : Wnt signaling determines endothelial progenitor cell fate and modulates the neovascularization through the regulation of endothelial progenitor cell metabolic profile (solid). Fenofibrate inhibits Wnt signaling in endothelial progenitor cells, regulates endothelial progenitor cell metabolism, and potentially prevents pathologic neovascularization (dash).